Manifestation of formal and informal code switching in Nairobi, Kenya - Jagero, Juliet A.; Odongo, Eston Kwach (SAVAP International, 2012)
This paper discusses Manifestations of Code Switching in Nairobi. The main objective is to examine the influence of Variables such as Formality and Informality of the conversation context in Code Switching and Code selection. The researcher tape- recorded spontaneous speech from the respondents, then the tape recorded data was transcribed on paper and the extracts from the transcribed text were analyzed based on the tenets of Speech Accommodation Theory and Markedness Model. The study has revealed that speakers Switch Codes in an attempt to exhibit their level of confidence, domination and also when they desired a need for social integration and approval. It was further revealed that Formal (English /Kiswahili)and Informal Codes (Sheng’/mother tongue) were used for different function, Formal Codes were used to convey a more official context and seriousness while Informal Codes were used for a relaxed context and lack of seriousness. It was therefore realized that each of the Codes has a specific function and social symbolism to each individual group.
Keywords: Formal; Informal Code switching in Nairobi